Rasa Syukur dengan Kesejahteraan Psikologis pada Mahasiswa Pekerja Universitas Pamulang - Cindy Kusumawati; Sifa Fauziah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Gratitude plays a crucial role in enhancing psychological well-being, particularly for students who balance work and studies. This research seeks to explore the connection between gratitude and psychological well-being among working students at Pamulang University. A quantitative approach was used, involving 107 respondents who were selected through purposive sampling and completed a Google Form survey. The data were analyzed using simple linear regression with SPSS 26 software. The analysis revealed a correlation coefficient of 0.824, showing a significant relationship between gratitude and psychological well-being. This suggests that higher levels of gratitude are associated with better psychological well-being. The study also highlights the significance of gratitude-based interventions to help working students manage stress and enhance their overall quality of life. Additionally, this research contributes to the field of positive psychology, particularly within Indonesia's higher education context, and offers practical recommendations for universities to develop programs that more effectively support the well-being of working students.